Penggunaan Theory of Planned Behavior dalam Kajian Perilaku Konsumen Hijau - Rizka Zulfikar; Nanang Suryadi; Yuditha Valen Prasarry; Sarah Barqiah; Dedy (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
This study aims to evaluate the use of the Theory of Planned Behavior (TPB) in the analysis of green consum-er behavior. The TPB were an important framework for understanding consumer behavior, emphasizing the role of intention in shaping action, with factors such as attitudes, subjective norms, and perceived behavioral control. This research was conducted through a literature review using 26 articles from leading interna-tional journals such as Elsevier, Springer, Emerald, Taylor & Francis, Wiley Online, and Sage from 2013 to 2023.The results showed that the use of TPB in analyzing the purchasing behavior of environmentally friend-ly products provides strong evidence that intention influences consumer behavior. Other factors such as trust in the product also influence buying behavior. The advantages of the TPB lie in a structured framework, identification of behavioral influence factors, and support for effective marketing strategies. However, TPB have limitations, such as the inability to explain impulsive behavior and the inability to adequately incur-porate contextual factors. To address this, Extended-TPB, which includes additional variables, and the integration of TPB with other theories have developed. This increases understanding of environmentally friendly consumer behavior. The use of TPB and development has resulted in thousands of research articles published in various leading international journals. This confirms that TPB remain a significant focus of re-search in understanding consumer behavior in the context of sustainability.